An Investigation into the Factors which Determine Farmers'Acceptance of Supply Contracts: The Ethanol Beet Example - Oliver Mußhoff; Norbert Hirschauer; Markus Fahlbusch (German Journal of Agricultural Economics (GJAE), 2014)
Little is known about the actual behavior of farmers who are offered forward contracts for renewable resources. The present survey explores farmers' acceptance of sugar beet supply contracts. We find that the farmers' responses are not in line with forecasts that are based on critical prices derived from naiv̈e gross margin comparisons. Instead, farmers take into account that the contractual obligation to supply a certain amount of beets in combination with the volumetric production risk produces an asymmetry in revenues. They also consider risk and dynamic changes of the relative competitiveness of sugar beet and competing crop alternatives. We furthermore find that the past matters: a subsequent improvement of a contract offer that is made after an initial offer has been rejected by farmers finds lower acceptance than an initially better offer.
Keywords: 330; Biokraftstoff; Agrarprodukt; Lieferantenbewertung; Landwirte; Deutschland